2020
DOI: 10.1681/asn.2020050558
|View full text |Cite
|
Sign up to set email alerts
|

AKI and Collapsing Glomerulopathy Associated with COVID-19 and APOL 1 High-Risk Genotype

Abstract: BackgroundKidney involvement is a feature of COVID-19 and it can be severe in Black patients. Previous research linked increased susceptibility to collapsing glomerulopathy, including in patients with HIV-associated nephropathy, to apo L1 (APOL1) variants that are more common in those of African descent.MethodsTo investigate genetic, histopathologic, and molecular features in six Black patients with COVID-19 presenting with AKI and de novo nephrotic-range proteinuria, we obtained biopsied kidney tissue, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
281
7
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(306 citation statements)
references
References 30 publications
11
281
7
7
Order By: Relevance
“…From the same group, 3 patients, all African American (AA), out of 161 patients with CoV-AKI with findings suggestive of glomerular disease underwent kidney biopsy which revealed collapsing glomerulopathy in each biopsy 6 . This is in line with emerging reports of collapsing glomerulopathy in AA individuals who are carriers of the Apolipoprotien L1 (APOL1) high risk genotype and acquire COVID-19 14 , 15 . Thus, collapsing glomerulopathy should be suspected in AA individuals presenting with AKI and new onset nephrotic range proteinuria, where the COVID-19 potentially serves as a second hit.…”
Section: Acute Kidney Injurysupporting
confidence: 90%
“…From the same group, 3 patients, all African American (AA), out of 161 patients with CoV-AKI with findings suggestive of glomerular disease underwent kidney biopsy which revealed collapsing glomerulopathy in each biopsy 6 . This is in line with emerging reports of collapsing glomerulopathy in AA individuals who are carriers of the Apolipoprotien L1 (APOL1) high risk genotype and acquire COVID-19 14 , 15 . Thus, collapsing glomerulopathy should be suspected in AA individuals presenting with AKI and new onset nephrotic range proteinuria, where the COVID-19 potentially serves as a second hit.…”
Section: Acute Kidney Injurysupporting
confidence: 90%
“…49,50 Therefore, these delays meant that most patients in our cohort may have cleared virus from their kidney and were therefore RT-PCR negative by nasopharyngeal J o u r n a l P r e -p r o o f swab at the time of biopsy. Even with this caveat, most recent biopsy and autopsy case series have concluded that there is no significant SARS-CoV-2 infection of the kidney, 16,20,24,48,[51][52][53] which is in contrast to the possibility of direct infection that was reported in two earlier studies. 11,45 Therefore, our study adds to the accumulating evidence that direct and persistent infection of the kidney by SARS-CoV-2 does not appear to play a significant role in kidney disease in most COVID-19 patients.…”
Section: Discussionmentioning
confidence: 82%
“…Many viral infections can cause FSGS including human immunodeficiency virus 1 (HIV-1), cytomegalovirus, parvovirus B19 and Epstein-Barr virus [8,9]. Histologically, the collapsing variant shows segmental or global mesangial consolidation and loss of endocapillary patency in association with extra-capillary epithelial hypertrophy and/or proliferation [8].…”
Section: Discussionmentioning
confidence: 99%